(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research on tautology in written and spoken English: A case of Nigerian users was carried out to bridge the gap in the widely used and accepted tautologies by Nigerian speakers of English with particular interest in proffering the standard usage of such tautologies, notwithstanding the fact that the English spoken in Nigeria is not totally standardised. To achieve this, thirty final year students of the department of English, Akwa Ibom State University were interviewed in written and spoken English. Every day topic of discussion was painstakingly selected and administered so that it could be discussed both in speaking and writing activities. Excerpts of discussions on social media platforms were also extracted. Austin’s Speech Acts theory was adopted as the theoretical framework with particular attention to its taxonomies. Data obtained were analyzed and findings show that tautologous usages have become part of their language habit and other Nigerian users of English unconsciously as they pay little or no attention to it, given that it has been widely used. The paper thus suggests that tutors in classroom settings, media presenters, language teachers in all spheres should be on deck; seminars, and other means of enlightenment be conducted pointing out the errors and the standard versions.